Mainstreaming social determinants of health (SDH) terms into the PubMed database would facilitate effective scrutiny of SDH - Yegnanarayana Iyer Saraswathy Sivan (Social Medicine Publication Group, 2014)
Background: Scrutiny of social determinants of health (SDH) is a vital link that bridges social sciences and public health sciences. The effective scrutiny of SDH warrants scrutiny of specific social risk factors of diseases. A major handicap in the scrutiny of SDH is the lack of a strong and common platform for researchers from both social sciences and public health sciences. Improving research infrastructure with in-built provision for interface between the sciences is a pre-requisite for facilitating evidence-based research, and this includes unfettered access to searchable databases. Though there are a few databases which offer interface for both sides, at present, PubMed seems to be the only freely accessible database in this regard. Rationale: However, PubMed needs to be mainstreamed with more SDH terms to make scrutiny of SDH comprehensive as well as evidence-based. Improving search and retrieval strategies of the database to better extract knowledge in the broad domain of SDH is suggested. Objectives: This paper suggests steps to strengthen the PubMed database by mainstreaming its current features such as Automatic Term Mapping, MeSH, and the creation of an exclusive sub-set on SDH. Summary: Mainstreaming SDH terms into the PubMed database would facilitate effective scrutiny of SDH and the creation of an evidence-base on SDH without much investment. Research output based on an evidence-based, SDH-mainstreamed PubMed database would in turn, facilitate mainstreaming research protocols and papers, and policy and programme documents with SDH terms, thereby making scrutiny of SDH more effective. This is the first time that such a proposal for mainstreaming the PubMed database with SDH terms is being mooted. When implemented, its results are expected to be not only positive but also far-reaching across the disciplines involved in the scrutiny of SDH.